Aggregation Validation Approach for the Management of Resources in a Smart Grid - Spínola, João (2016)
Power systems evolution to an intelligent energy system – smart grid, encounters several issues when integrating distributed generation and demand response. At the aggregator level, activities such as the energy resource management, capacities aggregation and resources remuneration are needed. The present paper addresses the previous needs of the aggregator by considering an optimization of the resources scheduling, followed by an aggregation of resources, and their remuneration is performed. The considered case study is composed by 20 suppliers, 548 distributed generators and 20310 consumers participating in three distinct demand response programs: load reduction, curtailment and real-time pricing.